2022
DOI: 10.1128/iai.00267-22
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of sncRNA Improves the Protective Efficacy of Outer Membrane Vesicles against Helicobacter pylori Infection in a Mouse Model

Abstract: The outer membrane vesicles (OMVs) secreted by Helicobacter pylori contain various bacterial components, such as proteins, phospholipids, toxins, and nucleic acids, including small noncoding RNA (sncRNA), which have regulatory functions in cell envelope structure, metabolism, bacterial communication, biofilm formation, and virulence. We previously showed that knocking out sncRNAs sR-989262 and sR-2509025 at the cellular level increased interleukin 8 (IL-8) levels in mice exposed to OMVs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…IL-12 and IL-4 are critical cytokines in the Th1 and Th2 cellular immune responses, respectively [ 11 ]. The IL-12 and IL-4 levels were also significantly higher in all OMV-immunized groups presenting the UreB antigen than in the control group, indicating that OMV immunization triggered both Th1 and Th2 cellular immune responses in mice, consistent with previous results ( Figures 4b, f, c, g ).…”
Section: Resultsmentioning
confidence: 99%
“…IL-12 and IL-4 are critical cytokines in the Th1 and Th2 cellular immune responses, respectively [ 11 ]. The IL-12 and IL-4 levels were also significantly higher in all OMV-immunized groups presenting the UreB antigen than in the control group, indicating that OMV immunization triggered both Th1 and Th2 cellular immune responses in mice, consistent with previous results ( Figures 4b, f, c, g ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown how genetic manipulations can be easily performed with the aim to further improve OMV safety, immunogenicity, and protective efficiency. For example, it has been shown that disruption of small noncoding RNA improves the protective efficacy of OMVs against Helicobacter pylori infection in a mouse model [ 72 ]. Both intranasal and intraperitoneal immunization with flagellin-deficient S. typhimurium OMVs resulted in efficient protection against heterologous S. choleraesuis and S. enteritidis challenge [ 73 ] and immunization with OMVs from major outer membrane protein-deficient S. typhimurium mutants enhanced cross-protection [ 74 ].…”
Section: Trends Emerging In Preclinical Studiesmentioning
confidence: 99%
“…Antibody levels in mouse blood samples and vaginal secretions were quantified using quantitative ELISA as described previously 41 . OMP (1 mg) suspended in 100 mL of sodium carbonate buffer (pH 9.6) was used to coat each well of a 96-well plate (Nalge Nunc Inc., Naperville, IL, USA) that was incubated overnight at 4 °C.…”
Section: Elisamentioning
confidence: 99%